IMPACT OF PARENT INVOLVEMENT ON SECONDARY SCHOOL STUDENT’S ACADEMIC PERFORMANCE IN SAMTSE DISTRICT, BHUTAN - -, Singye; Leksansern, Arisara (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of the study was to determine and address the impact of parent involvement on student academic performance, the levels of parent involvement of secondary schools, the levels of secondary school student academic performance, and the relationship between parent involvement on secondary school student academic performance in Samtse district, Bhutan. The type of parent involvement in the lives of adolescent high school students and its relationship to student academic performance factors of student engagement, attendance, and attitude toward school was researched so as to provide secondary school managers with the awareness essential to suggest recommendation to the parent community. The researcher employed quantitative research methodology and a questionnaire was used to collect data from the total population of 220 grade XI students studying in three higher secondary schools. The data was analyzed using descriptive statistics including Mean (X̅) and standard deviation (SD), Pearson’s coefficient correlation, and simple regression analysis. Thus, this study found that there is a relationship between parent involvement types of parenting, communicating, decision making and learning at home and the student academic performance factors of engagement, attendance and attitude toward school. This study showed that the greatest relationship between parent involvement types and the student performance factors came from the influence that parents exert on adolescent children at home. Expectations, as well as care and concern, form a two-pronged approach that parents can use to impact the relationship between involvement type and student performance. The relationship between parents’ expectations, care and concern with the student performance factors of engagement, attendance and attitude toward school is solid enough to be suggestive of predictability. Therefore, parents should continue to express their expectations and care and concern for their children as they enter secondary school. Future researches were suggested to choose more sample schools including primary schools and in schools in different locations such as urban, rural and remote areas and explore other factors that affect students’ overall performance.